Differences between English Deixes Used by the Speaker and Indonesian Subtitles Made by the Television Station (Case Study of Angelina Sondakh’s Interview on Rosi Kompas TV) - Lysbeth Sirait; Frederik Agnar Widjaja (Universitas Cokroaminoto Palopo, 2023)
This research paper aims at examining the differences between English utterances expressed by the speaker on a live television show and the Indonesian subtitles made by the television station. The objects to be analyzed are personal, spatial, and discourse deixis in the form of speech. The writer takes the data from Rosi talk show on Kompas TV with Angelina Sondakh. The design of the study uses descriptive qualitative methods and documentation methods to get the data. In exploring the types of deixes and subtitles, the writer uses pragmatic analysis, especially deixis theory, and translation theory. During the show, the speaker often mixed up Indonesian with English. Therefore, the station made quick subtitles in Indonesian when the speaker was speaking a total or partial sentence of English. Most differences happen to be in deictic forms; when the speaker only mentioned something deictically in English, the station made a clear and distinguished reference in Indonesian. The research findings of the study show that there is a total of 23 differences, which occur in discourse (61%), personal (35%), and spatial deixis (4%), which translated into similar forms and identical expressions.